Ergonomic Education to Reduce the Risk of Musculoskeletal Disorders - Indriyani Indriyani; Rury Tiara Oktariza; Noviyanti Noviyanti; Mochammad Nanda Ardani Alfath; Adinda Fatimah Azahra (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Workers are mainly human resources with a significant influence on the production process, in particular manual work. Activities in manual material handling include carrying, lifting, lowering, pushing, and pulling loads. Transport labor is one type of work that requires energy and great muscle strength and a strong physique to carry the load at work. Workers who are in the wrong position during prolonged work will increase the risk of musculoskeletal complaints. The purpose of this community service activity is to provide ergonomic education to reduce the risk of Musculoskeletal Disorders. Methods: This service activity uses counseling methods, leaflet giving, demonstrations, simulations, and discussions. The participants were given questionnaires before and after educational activities, namely ergonomics knowledge questionnaires to determine the level of ergonomics knowledge and also musculoskeletal complaint questionnaires. Results: This activity was attended by 21 participants who were all male. In the knowledge variable, the mean pre-test value was 56.67 and the post-test was 68.57. In the Musculoskeletal complaint variable, the mean pre-test value was 30.05 and the post-test was 28.76. Conclusion: Based on the results of the pre-test and post-test, shows that ergonomics education can help improve ergonomic knowledge and reduce the risk of musculoskeletal disorders in workers.